Implementation of Electronic Medical Records in Ensuring the Completeness of Informed Consent Forms for Caesarean Section Procedures - Dwi Prastya; Yayang Ayu Nuraeni (Faculty of Medicine, Universitas Tadulako, 2026)
Background: Electronic Medical Records (EMR) have been widely adopted to improve the quality and accessibility of medical documentation, including informed consent forms for surgical procedures. Objective: This study aims to analyze the completeness and accuracy of informed consent documentation for caesarean section procedures following EMR implementation at Hospital X. Methods: This is a qualitative study involving 54 informed consent forms collected from November 2024 to February 2025. Data were obtained through observation, document review, and in-depth interviews with medical record officers and clinical staff. Results: The study found that the average completeness rate of informed consent forms reached 96%, with missing elements such as patient address (9%) and witness signatures (15–32%). While key clinical components were fully documented, issues related to data accuracy, return timeliness, and legal authentication remained. Suboptimal utilization of EMR features and limited awareness of legal documentation procedures were contributing factors. Conclusion: Despite the benefits of EMR in structuring documentation, its implementation alone does not guarantee complete, accurate, and legally valid informed consent. Enhancing SOP adherence, digital system optimization, and staff training in legal-medical documentation are necessary to improve record quality.